The Influence of Religious Affiliation and Church Attendance on Climate Change Awareness, Perception, and Action: The Role of Churches through Environmental Education in Nigeria - George C. Nche (Didaktika: Jurnal Kependidikan, 2023)
Churches can serve as platforms for environmental education, fostering a sense of responsibility towards the environment among their congregations.This study examined the influence of religious affiliation and attendance on climate change awareness, perception, action and perceived role of the church through environmental education in Nigeria. Churchgoers from Catholic, Anglican, and Pentecostal churches from the six geopolitical zones of Nigeria completed the Climate Change Awareness Questionnaire (CCAQ); Climate Change Perception Questionnaire (CCPQ); Churches’ Role Perception Scale (CRPS); and Climate Change Action Assessment Scale (CCAAS) and also provided relevant demographic information. Results of statistical analysis indicated that there was a significant difference between the religious denominations in climate change awareness, perception, action and perceived role of the church. The results also showed that more frequency of attendance to church activities was associated with increased climate change awareness, perception of climate change, climate change action, and perceived role of the church in addressing climate change. Churches must continue incorporating environmental teachings into their religious practices and advocating for environmentally-friendly behaviors among members as ways of contributing to the campaign against climate change.